Catalyst–Support Interaction in Polyaniline-Supported Ni3Fe Oxide to Boost Oxygen Evolution Activities for Rechargeable Zn-Air Batteries - Zou, Xiaohong; Lu, Qian; Tang, Mingcong; Wu, Jie; Zhang, Kouer; Li, Wenzhi; Hu, Yunxia; Xu, Xiaomin; Zhang, Xiao; Shao, Zongping; An, Liang (Nano-Micro Letters, 2024)
Catalyst–support interaction plays a crucial role in improving the catalytic activity of oxygen evolution reaction (OER). Here we modulate the catalyst–support interaction in polyaniline-supported Ni3Fe oxide (Ni3Fe oxide/PANI) with a robust hetero-interface, which significantly improves oxygen evolution activities with an overpotential of 270 mV at 10 mA cm−2 and specific activity of 2.08 mA cmECSA−2 at overpotential of 300 mV, 3.84-fold that of Ni3Fe oxide. It is revealed that the catalyst–support interaction between Ni3Fe oxide and PANI support enhances the Ni–O covalency via the interfacial Ni–N bond, thus promoting the charge and mass transfer on Ni3Fe oxide. Considering the excellent activity and stability, rechargeable Zn-air batteries with optimum Ni3Fe oxide/PANI are assembled, delivering a low charge voltage of 1.95 V to cycle for 400 h at 10 mA cm−2. The regulation of the effect of catalyst–support interaction on catalytic activity provides new possibilities for the future design of highly efficient OER catalysts. Highlights: 1 Ni3Fe oxide, with an average size of 3.5 ± 1.5 nm, was successfully deposited onto polyaniline (PANI) support through a solvothermal strategy followed by calcination. 2 The catalyst–support interaction between Ni3Fe oxide and PANI can enhance the Ni-O covalency via the interfacial Ni-N bond. 3 Ni3Fe oxide/PANI-assembled Zn-air batteries achieve superior cycling life for over 400 h at 10 mA cm−2 and a low charge potential of around 1.95 V.